Serum lipid changes during anticonvulsive treatment Serum lipids in epileptic children - Yilmaz, E; Dosan, Y; Gurgöze, MK; Güngör, S (Acta Medica Belgica, 2001)
Serum lipid profile changes were investigated in 53 children receiving phenobarbital (n = 14), carbamazepine (n = 21), and valproic acid (n 18) for their newly, diagnosed seizure disorder. The patients were,followed prospectively. Serum total cholesterol, high-density, lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglyceride concentrations increased after 3 months of treatment with carbainazepine and remained high after one year Serum total cholesterol levels increased after 3 months of treatment with phenobarbital and remained high after one year Serum lipid concentrations did not change during valproic acid therapy. Serum lipid profiles should be carefully, monitored in children receiving enzyme inducing antiepileptic drugs.
Keywords: epilepsy; anticonvulsants; hyperlipidemia; atherosclerosis